Microplastic Fiber Emissions From Wastewater Effluents: Abundance, Transport Behavior and Exposure Risk for Biota in an Arctic Fjord - Herzke, Dorte; Ghaffari, Peygham; Sundet, Jan Henry; Tranang, Caroline Aas; Halsband, Claudia (Frontiers in Environmental Science, 2021)
Microfibers are one of the major classes of microplastic found in the marine environment on a global scale. Very little is known about how they move and distribute from point sources such as waste water effluents into the ocean. We chose Adventfjord near the settlement of Longyearbyen on the arctic Svalbard archipelago as a case study to investigate how microfibers emitted with untreated wastewater will distribute in the fjord, both on a spatial and temporal scale. Fiber abundance in the effluent was estimated from waste water samples taken during two one week periods in June and September 2017. Fiber movement and distribution over time was then modelled (with FVCOM integrated into the OpenDrift model) for the water column and the seafloor in the fjord for negatively buoyant ('light), neutrally buoyant ('neutral), buoyant ('heavy') and sinking ('very heavy') fibers, equivalent to fibers of different plastic polymers and wool. The results clearly show the large impact of the hydrodynamics in the fjord on fiber distributions, and different behavior of different fiber types. While light fibers remain in the surface layers and leave the fjord quickly with outgoing currents, heavy fibers sink to the bottom and deposit in the inner parts of the fjord and along the northern shore. The southern shore, in contrast, is much less affected with low fiber concentrations throughout the study period. Fiber distributions were then compared with published pelagic and benthic fauna distributions at selected stations around the fjord. The ratios of fibers to organisms showed a very wide range, indicating hot spots of encounter risk for pelagic and benthic biota. This approach, in combination with in situ groundtruthing, can be instrumental in understanding microplastic pathways and fate in coastal areas and help authorities develop monitoring and mitigation strategies for microfiber and microplastic pollution in their local waters .